PENERAPAN PENDEKATAN SAINTIFIK DALAM PROSES PEMBELAJARAN EKONOMI DI SMA NEGERI 1 KOTA BANDA ACEH - Ruaida, Nana Suraiya, Nurul Fitria (Universitas Syiah Kuala, 2019)
ABSTRACTThe purpose of this research was to investigate (1) the implementing of a scientific approach to economic learning process which consists of observating, ask questions, gather information, associate, and communicate, (2) To find out the difficulties faced by teachers when applying a scientific approach in the economic learning process, (3) investigate the solution in overcoming difficulties in applying a scientific approach in Banda Aceh 1 Senior High School. This research uses a qualitative approach with research procedures descriptive data. Subjects in this research were 3 economic subject teachers, while the objects in this study were scientific approaches in the process of economic learning in Banda Aceh 1 Senior High School. Data collecting in this research used observation, interviews, and documentation.Data analysis techniques used are data reduction, data presentation, and conclusion or verification. Based on the results of this result it can be concluded that (1) The application of the scientific approach in the process of economic learning in Banda Aceh 1 Senior High School has been implemented since 2013 curriculum, but in its implementation it has not run optimally, (2) In general, in applying the scientific approach economics teachers only faced difficulty in the step of observing and asking questions because most students are difficult to understand when given teaching materials that they must observe themselves. Then training them to ask, where some students did not brave enough to ask the teacher questions about what they had observed. (3) The efforts or solutions made by teachers to overcome these difficulties are by giving motivation to students and providing explanations or understanding with language that is more easily knows and understood by students.Keyword : Scientific Approach, Economic Learning Process